Ground source heat pump systems in historical buildings: two Italian case studies. (October 2017) - Emmi, Giuseppe; Zarrella, Angelo; De Carli, Michele; Moretto, Stefano; Galgaro, Antonio; Cultrera, Matteo; Di Tuccio, Maria; Bernardi, Adriana
Abstract: Reducing the energy demand of buildings has become one of the key points of the European Union. The issue related to the air conditioning of old and historical buildings is nowadays one of the most important field of operation for the primary energy saving and, at the same time, for the reduction of the CO2 emission. The recent development of heat pump able to rise the supply of high temperature at the condenser side makes this technology suitable for the application also in historical buildings that are characterized by low thermal insulation and high thermal capacitance. In this context, the ground source heat pump systems can be used for both heating and cooling. The aim of this work is to analyze the thermal behavior of two historical buildings located in Italy, in Venice and Florence respectively. Detailed computer simulations of the buildings have been carried out by means of a transient calculation tool TRNSYS. Energy simulations of GSHP systems have been performed and a comparison with a common plant system using a gas boiler for heating and air-to-water chiller for cooling has been carried out.